Cross dimerization of amyloid-beta and alpha synuclein proteins in aqueous environment: a molecular dynamics simulations study - Jose, Jaya C.; Chatterjee, Prathit; Sengupta, Neelanjana (Plos One, 2014)
Self-assembly of the intrinsically unstructured proteins, amyloid beta (A beta) and alpha synclein (alpha Syn), are associated with Alzheimer's Disease, and Parkinson's and Lewy Body Diseases, respectively. Importantly, pathological overlaps between these neurodegenerative diseases, and the possibilities of interactions between A beta and alpha Syn in biological milieu emerge from several recent clinical reports and in vitro studies. Nevertheless, there are very few molecular level studies that have probed the nature of spontaneous interactions between these two sequentially dissimilar proteins and key characteristics of the resulting cross complexes. In this study, we have used atomistic molecular dynamics simulations to probe the possibility of cross dimerization between alpha Syn(1-95) and A beta(1-42), and thereby gain insights into their plausible early assembly pathways in aqueous environment. Our analyses indicate a strong probability of association between the two sequences, with inter-protein attractive electrostatic interactions playing dominant roles. Principal component analysis revealed significant heterogeneity in the strength and nature of the associations in the key interaction modes. In most, the interactions of repeating Lys residues, mainly in the imperfect repeats `KTKEGV' present in alpha Syn(1-95) were found to be essential for cross interactions and formation of inter-protein salt bridges. Additionally, a hydrophobicity driven interaction mode devoid of salt bridges, where the non-amyloid component (NAC) region of alpha Syn(1-95) came in contact with the hydrophobic core of A beta(1-42) was observed. The existence of such hetero complexes, and therefore hetero assembly pathways may lead to polymorphic aggregates with variations in pathological attributes. Our results provide a perspective on development of therapeutic strategies for preventing pathogenic interactions between these proteins.

Cloning, expression and in silico studies of a serine protease from a marine actinomycete (Nocardiopsis sp NCIM 5124) - Rohamare, Sonali; Gaikwad, Sushama M.; Jones, Dafydd; Bhavnani, Varsha; Pal, Jayanta; Sharma, Ranu; Chatterjee, Prathit (Process Biochemistry, 2015)
A serine protease (N. protease), from Nocardiopsis sp., was cloned and expressed in Escherichia coli and investigated for its potential kinetic stability. Protein expression using two vectors, pET-22b (+) and pET-39b (+) was compared based on proper folding and soluble expression of the protein. pET-39b (+) was found to be a better vector for soluble expression of this protease containing disulfide bonds. In silico studies were also carried out for N. protease. Homology modeling suggested N. protease to be a member of PA clan of proteases. The phylogenetic analysis showed relatedness of N. protease to kinetically stable proteases. Molecular docking studies performed exhibited interaction of a peptide substrate with catalytic pocket of the enzyme. High temperature MD simulations were performed on N. protease to study its unfolding behavior and comparisons were made with alpha LP. A novel approach to study `cooperativity' of protein unfolding was undertaken, wherein `P' value analysis based on phi and psi values of the protein was performed. Data showed sharper P value transition for alpha LP when compared to N. protease thus indicating relatively less kinetic stability of N. protease. Present study holds significance as the non-streptomycete actinomycetes group is least explored and ensures industrially important enzymes with exceptional stabilities. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Actinomycetes; Cloning and expression; Kinetic stability; Protease; Thermal simulation